Zero-distance Pulse Front and Its Application in Both Space and Time Optics - Gitin, Andrey (New Ideas Concerning Science and Technology Vol. 5, 2021)
The unfolding technique, based on the concept of the zero-distance pulse front, is used for calculation both aspherical focusing optical elements (in space optics) and reflective diffraction dispersive delay lines (in time optics).